286 MEASUREMENT OF ALL-TERRAIN VEHICLE SAFETY BEHAVIORS IN RURAL COMMUNITIES. Issue 1 (1st January 2007) - Aitken, M. E.; Mullins, S. H.; Nixon, J.; Graham, J.; Coben, J. H.; Helmkamp, J. C.
Abstract : Background: All-terrain vehicle (ATV) injury in children is an increasing and serious problem. Accurately measuring ATV use patterns is challenging because ATVs are often used in rural isolated areas. Observation of real-time use patterns and safety behaviors is important to fully develop community-based injury prevention strategies and interventions. Methods: Observational surveys similar to those used in car seat injury prevention campaigns were developed and piloted in high-risk rural areas of Arkansas. Three methods of sampling were used by local volunteers: direct interviews at stationary observation posts (M1), direct interviews by ATV users at random locations (M2), and indirect observation in high ATV use locations (M3). Survey volume and quality using these methods were tracked, along with risk factors demonstrated by ATV users. Results: A total of 303 observational surveys of ATV safety were obtained over a 3-month period. Surveys were completed under all three methods, including M1: n = 24, 7.9%; M2: n = 85, 28.1%; and M3: n = 194, 64%. Use of an observation station was low yield due to problems coordinating volunteer schedules and unpredictable weather. Indirect observation was found to be quickest and easiest for the volunteers and less intrusive than direct interview. Risky ATV use patterns included frequent exposure to full-size ATVs by children < 18 years old ( n = 101, 35.6%), riding with passengers ( n = 101, 35.6%), and low use of helmets ( n = 32, 10.6%) or any other safety equipment ( n = 161, 53.1%). Conclusions: Brief observational surveys can be effectively used to document ATV safety behavior and demonstrate impact of interventions, particularly in rural environments. Flexibility in sampling methods and use of community volunteers in different settings has provided valuable information on high-risk ATV use. These methods can form the basis for larger interventions for ATV injury prevention.